A comparative study of intravenous hydration and amnioinfusion for IUGR associated with oligohydramnios in pregnant women and fetomaternal outcome - Kumari, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ultrasound assessment of amniotic fluid has significant implication in obstetric care and it has become an integral and important component of pregnancy assessment. Methods: A prospective study done in all pregnant women (n=30) who had been diagnosed with oligohydromnios (with AFI<8 by Phelan’s method) by ultrasonography will be attending in obstetric gynecology department SMS Medical College, Jaipur will be selected according to inclusion or exclusion criteria (as per sample size) after written informed consent. Results: Higher incidence of preterm delivery in the i.v. infusion group as compared to the amino acid group and difference was significant (p value <0.05). In amnioinfusion group 3 cases (20.0%) had LSCS and in i.v. infusion group 6 cases (40.0%) had delivered by LSCS. The distribution of delivery mode did not differ significantly across two intervention groups (p value >0.05). Significantly higher proportion of cases from amino acid group had larger birth weight and significantly higher proportion of cases from i.v. infusion group had smaller birth weight (p value <0.001). Conclusions: This study points towards the use of intravenous hydration and amnioinfusion in increasing the liquor in oligohydramnios associated with IUGR and proves useful in reducing perinatal morbidity and mortality.